A new fluorescent dye for cell tracing and mitochondrial imaging in vitro and in vivo. Issue 9 (13th November 2015) - Press, Adrian T.; Ungelenk, Luisa; Rinkenauer, Alexandra C.; Gröger, Marko; Lehmann, Frank; Mosig, Alexander; Schubert, Ulrich S.; Clemens, Mark G.; Bauer, Michael
Abstract : Mitochondria contribute to redox and calcium balance, and apoptosis thus regulating cellular fate. In the present study, mitochondrial staining applying a novel dye, V07‐07059, was performed in human embryonic kidney cells, a human vascular endothelial cell line and primary human mononuclear cells. The new fluorescent mega Stokes dye (peak excitation: 488 nm, peak emission: 554 nm) showed superior fluorescent properties and stability. V07‐07059 stains mitochondria dependent on their membrane potential and is safe to use in vitro and in vivo . Unlike other dyes applied in this context (e.g. Tetramethylrhodamine methyl ester), V07‐07059 only marginally inhibits mitochondrial respiration and function. V07‐07059 enables real time imaging of mitochondrial trafficking and remodeling. Prolonged staining with V07‐07059 demonstrated the dyes suitability as a novel probe to track cells. In comparison to the widely used standard for cell proliferation and tracking studies 5(6)‐diacetate N‐succinimidyl ester, V07‐07059 proved superior regarding toxicity and photostability. Abstract : Mitochondria contribute to redox and calcium balance, and apoptosis thus regulating cellular fate. In the present study, mitochondrial staining applying a novel dye, V07‐07059, was performed in human embryonic kidney cells, a human vascular endothelial cell line and primary human mononuclear cells. The new fluorescent mega Stokes dye showed superior fluorescent properties and stability. In comparison to the widely used standard for cell proliferation and tracking studies 5(6)‐ diacetate N‐succinimidyl ester, V07‐07059 proved superior regarding toxicity and photostability.